The Influence of Interest Rates and Exchange Rates on Inflation in Indonesia - Yasa, Putri Suci; Damayanti, Elfi; Farrel, Muhammad Daffa; Rizaldi, Muhammad; Sigalingging, Kasah (Economic: Journal Economic and Business, 2024)
One of the problems in the economy in every country is the problem of inflation. Inflation is the process of increasing general goods which are basic goods needed by the community continuously. This study aims to see the factors that influence the inflation rate in Indonesia. The data used are secondary data obtained through the Provincial Central Statistics Agency. The data taken are inflation (Y), interest rates (X1), and exchange rates (X2) during the period 2015-2024. The research method used in this study is the time series method. The results of the analysis show that interest rates (X1) and exchange rates (X2) have a negative and significant effect on the inflation rate in Indonesia.